Synthesis, Computational Studies and Preliminary Pharmacological Evaluation of New Arylpiperazines. Issue 3 (2011) - Kumar, Sushil; Wahi, A. K.; Singh, Ranjit
Abstract : A series of novel arylpiperazines were synthesized and the target compounds evaluated for atypical antipsychotic activity in apomorphine induced climbing behavior (D2 antagonism), 5-HTP induced head twitches (5-HT2A antagonism) and catalepsy studies in albino mice. The physicochemical similarity of the target compounds with respect to standard drugs clozapine, ketanserine and risperidone was assessed by calculating from a set of physiochemical properties using software programs. The test compounds (3a-j) demonstrated good similarity values with respect to the standard drugs. Among them, compound 3d has emerged as an important lead compound showing potential atypical antipsychotic like profile.